2015
DOI: 10.1101/020305
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pangenome-wide and molecular evolution analyses of thePseudomonas aeruginosa species

Abstract: 30Background. Drug treatments and vaccine designs against the opportunistic human pathogen Pseudomonas aeruginosa have multiple issues, all associated with the diverse genetic traits present in this pathogen, ranging from multi-drug resistant genes to the molecular machinery for the biosynthesis of biofilms. Several candidate vaccines against P. aeruginosa have been developed, which target the outer membrane proteins; however, 35 major issues arise when attempting to establish complete protection against this … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 56 publications
2
30
0
Order By: Relevance
“…Comparative genomics among closely related bacterial strains has uncovered a plethora of proviruses of both temperate and chronic lifestyles [22][23][24]. The large genome of the opportunistic pathogen P. aeruginosa is no exception [25][26][27]. Each sequenced strain reveals multiple proviral genomes of both the temperate and chronic lifestyles, each in both active and inactive (latent) forms [28].…”
Section: Introductionmentioning
confidence: 99%
“…Comparative genomics among closely related bacterial strains has uncovered a plethora of proviruses of both temperate and chronic lifestyles [22][23][24]. The large genome of the opportunistic pathogen P. aeruginosa is no exception [25][26][27]. Each sequenced strain reveals multiple proviral genomes of both the temperate and chronic lifestyles, each in both active and inactive (latent) forms [28].…”
Section: Introductionmentioning
confidence: 99%
“…Given the huge diversity of bacterial genomes and functional capacities even within one species, the pathogen itself could account for 4 unexplained heterogeneity in the clinical course and outcome of sepsis. Recently, the pangenome of the species P. aeruginosa was estimated to contain more than 16,000 non-redundant genes, while only 15% of these genes were present in all strains forming the core genome (Mosquera-Rendon et al 2016). Of particular interest are prognostic bacterial biomarkers that can indicate the risk of a fatal outcome in septic patients, thus providing guidance in therapy and improved management of patient monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Mosquera-Rendon et al reported on the pangenome characterisation of 200 P. aeruginosa bacterial genomes. They found that approximately 60% of the P. aeruginosa genome was variable across the strains [110]. In this accessory genome, Pohl et al identified genes from other bacterial species [111].…”
Section: Update On P Aeruginosa Blood Stream Infectionmentioning
confidence: 99%
“…With the utilisation of whole genome sequencing we have been able to gain greater understanding of the genome of P. aeruginosa. It is a large genome of 6.3 MB, containing on average more than 6175 genes [110]. The core genome represents on average 88% of the genome [112].…”
Section: Introductionmentioning
confidence: 99%